Hematological disorders after renal transplantation: A single-center study (Annals of Medical Research, 2023)
Aim: Post-transplantation anemia (PTA) and post-transplantation erythrocytosis (PTE) are the most common hematological problems in patients after renal transplantation. Hematological disorders need to be corrected to improve the mortality and morbidity status of patients and to maintain cardiac and graft functions. The objective of this study is to determine the prevalence of PTA and PTE in kidney transplant (KT) patients in our region in our organ transplant center.Materials and Methods: 212 renal transplant patients who underwent KT in a single center between 2012 and 2020 were included in the study. Demographic, clinical, and laboratory data of renal transplant patients at preoperative and postoperative months 6 and years 1, 2, 3, 4, and 5 were evaluated.Results: We determined the prevalence of PTA to be 28.16% (Early PTA 25.62%), and the prevalence of PTE to be 4.22%. The PTA group consisted of 40 patients, 33 females and 7 males, with a mean age of 30.5 years, while the PTE group consisted of only 6 male patients with a mean age of 21. Female predominance was observed in the PTA group (33, 82.5%), and male predominance (6, 100%) was observed in the PTE group. While there was no correlation between PTA and graft loss, there was a statistical correlation between PTE and graft loss (p0.05). We found a negative correlation between hemoglobin levels and urea and a positive correlation between albumin, Ca, and tacrolimus levels.Conclusion: PTA is a common condition, especially in female patients, and its prevalence increases over the years if the necessary care is not taken in the follow-up, and complications that may occur can be prevented with early diagnosis and treatment. Even if the prevalence of PTE is low, especially young male patients should be followed, and treatment should be started early to prevent a possible complications.
Keywords: Kidney transplantation (KT); Post-transplantation anemia (PTA); Post-transplantation erythrocytosis (PTE); Hemoglobin